Synthesis of 3H, 13C, 2H3, 15N and 14C‐labelled SCH 466036, a histamine 3 receptor antagonist. (February 2015) - Hesk, D.; Borges, S.; Dumpit, R.; Hendershot, S.; Koharski, D.; Lavey, C.; McNamara, P.; Voronin, K.
<x xml:space="preserve">Abstract</x> The synthesis of [3H]SCH 466036, [Me‐3H3]SCH 466036, [13C, 2H3, 15N]SCH 466036 and [14C]SCH 466036 is described. [3H]SCH 466036 was prepared in two steps via Raney Ni‐catalysed exchange with tritiated water. [Me‐3H3]SCH 466036 was prepared in a single step from [3H]methyl iodide in 45% yield. [13C, 2H3, 15N]SCH 466036 was prepared in two steps from [15N]hydroxylamine and [13C, 2H3]methyl iodide with an overall yield of 16%. [14C]SCH 466036 was prepared in seven steps from [14C]potassium cyanide in an overall yield of 13%.